Guillain-Barre Syndrome in A Patient with Infectious Endocarditis: Clinical Observation and Literature Review - E. V. Reznik; P. A. Mogutova; M. Kh. Shurdumova; E. V. Astashkevich; A. L. Lukyanov; L. M. Mikhaleva; K. Yu. Midiber; A. P. Smirnov; G. N. Golukhov (Архивъ внутренней медицины)
Guillain-Barré Syndrome is a severe autoimmune disease of the peripheral nervous system, representing the most common cause of acute flaccid tetraparesis, which can lead to life-threatening respiratory failure in the absence of adequate therapy. The relationship between GBS and infective endocarditis is not well studied.A 54-year-old patient experienced increasing numbness and weakness in the lower extremities two weeks after an acute respiratory viral infection, and was hospitalized with suspected ischemic stroke. Brain computed tomography revealed no data for acute focal pathology but showed left-sided sinusitis and ethmoiditis. Cerebrospinal fluid analysis showed protein at 0.8 g/L (normal up to 0.2 g/L), with cytosis within normal limits. The neostigmine test was negative. The clinical and instrumental picture was assessed as Guillain-Barré Syndrome. Echocardiography revealed vegetations on the mitral valve (MV) leaflets, rupture of the anterior leaflet chordae (“flail leaflet” of the MV), and grade 3 mitral regurgitation. Despite ongoing therapy, including antibacterial and immunomodulatory treatment, the patient continued to exhibit neurological symptoms, developed pulmonary artery thromboembolism, nosocomial bilateral polysegmental pneumonia, and sepsis, leading to a fatal outcome. Autopsy confirmed infective endocarditis with rupture of the MV chordae, abundant growth of Pseudomonas aeruginosa, scant growth of Klebsiella pneumoniae and Acinetobacter baumannii, and right atrial thrombosis. No pathological changes were found in the brain substance.Thus, Guillain-Barré Syndrome in rare cases can be associated with infective endocarditis and negatively impact the course and prognosis of the disease.